Penerapan Sanksi Pidana Terhadap Oknum Kepolisian Negara Republik Indonesia Satuan Lalu Lintas Yang Melakukan Pungutan Liar Terhadap Pengemudi Kendaraan Bermotor Di Wilayah Hukum Kepolisian Resor Kota Pekanbaru - Rori Oktavian Saputra; Erdianto Effendi; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Law and lawlessness can be said as one unity that can not be separated from each other.Amid the implementation of the functions, duties and authority of the Traffic Police itself thereare violations committed by some elements of the Police Traffic Unit is a Wild Charge. In fact,individuals who perform these illegal fees are only given disciplinary sanctions andadministrative sanctions only. The purpose of writing this thesis, namely; First, the cause ofillegal levies committed by the elements of the Traffic Police Unit in the jurisdiction of thePekanbaru City Police Resort, Second, the application of sanctions to overcome the problem ofillegal levies conducted by the police of the Traffic Unit in the jurisdiction of Pekanbaru CityPolice.This type of research can be classified in sociological law research, ie researchconducted directly on the location or object of research that want to see between the correlationof law and society, so as to reveal the effectiveness of law enforcement in society and identify theunwritten law applicable to society. This research was conducted at Pekanbaru PekanbaruResort Police, while population and sample were all parties related to the problem studied inthis research, data source used primary data and secondary data, data collecting technique inthis research by interview and literature study.From the results of research problems there are two main things that can be concluded.First, the factors causing the illegal levies committed by the elements of the Traffic Police Unitin the jurisdiction of the Pekanbaru City Police Resort, among others, are from the personal andfrom outside the personal person of the perpetrator. Second The application of sanctions toovercome the problem of illegal levies conducted by the Traffic Police Persons in PekanbaruCity Police Precinct is not applied due to many reasons such as small nominal, the regulationsused are internal Police regulations and illegal charges are considered not a crime. Suggestionof the writer, Firstly, Applying criminal sanction based on Article 12 letter e, Law Number 20Year 2001 Amendment to Law Number 31 Year 1999 concerning Eradication of Corruption ofCriminal Police Persons who conduct illegal charges against motor vehicle drivers in the regionLaw of Pekanbaru City Police Resort. Secondly, it is hoped that the existence of criminalsanction can give a deterrent effect to the Traffic Police officers who conduct illegal charges inorder not to repeat the practice of illegal levies, especially in the jurisdiction of Pekanbaru CityPolice. Third, ask the government to establish a clearer regulation or law to regulate thepractice of illegal levies, given the increasingly rampant illegal charges in Indonesia.Keywords: Criminal Sanctions - Police - Wild Charges